2009
DOI: 10.1101/lm.1245009
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of dopamine D1 receptor and MEK signaling pathway in the ventromedial prefrontal cortex in consolidation and reconsolidation of recognition memory

Abstract: We investigated MEK and D1 receptors in the ventromedial prefrontal cortex (vmPFC) in consolidation and reconsolidation of recognition memory in rats nonhabituated to the experimental context (NH) or with reduced arousal due to extensive prior habituation (H). The D1 receptor antagonist enhanced consolidation and impaired reconsolidation in NH but impaired consolidation with no effect on reconsolidation in H. The D1 receptor agonist had no effect on consolidation in either H or NH but impaired reconsolidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…In this study, K252a and BDNF ASO blocked BDNF signaling and de novo synthesis, respectively, and we observed that BDNF in the IC, but not in the CeA, is functionally necessary for CTA memory reconsolidation. While most studies of reconsolidation were focused on consolidation, and the molecular mechanism and cellular substrates of consolidation and reconsolidation were largely shared, several studies have reported dissociations between these processes for particular plasticity molecules or for plasticity in general within certain brain regions [5], [10], [28], [29], [30], [31]. Our study further demonstrated that BDNF signaling in the IC and CeA played different roles in memory reconsolidation and consolidation.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, K252a and BDNF ASO blocked BDNF signaling and de novo synthesis, respectively, and we observed that BDNF in the IC, but not in the CeA, is functionally necessary for CTA memory reconsolidation. While most studies of reconsolidation were focused on consolidation, and the molecular mechanism and cellular substrates of consolidation and reconsolidation were largely shared, several studies have reported dissociations between these processes for particular plasticity molecules or for plasticity in general within certain brain regions [5], [10], [28], [29], [30], [31]. Our study further demonstrated that BDNF signaling in the IC and CeA played different roles in memory reconsolidation and consolidation.…”
Section: Discussionsupporting
confidence: 57%
“…Of note, an unequal recruitment of these brain regions, which are heterogeneously exposed to noradrenaline (van Veldhuizen et al 1994), has been documented during consolidation and reconsolidation of the same type of memory (Taubenfeld et al 2001;Garcia-Delatorre et al 2010). For instance, the prefrontal cortex can be differentially recruited during these memory phases depending on the arousal level induced by the task to be performed (Maroun and Akirav 2009). Of potential relevance to the present set of results is the higher expression of a1-adrenergic receptors in the latter area relative to that found in hippocampus and amygdala (Rainbow and Biegon 1983;Nicholas et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…von Hertzen et al, 2005; Maroun & Akirav 2009; Taubenfeld et al, 2001; Lee et al, 2004, 2008a, 2010; reviewed in Alberini 2005). Furthermore, several reconsolidation studies have shown that as time passes memories become resistant to reconsolidation blockers (Milekic et al, 2002; Suzuki et al, 2004; Eisenberg et al, 2004), though others have found conflicting results (Debiec et al, 2002; Wang et al, 2009; Robinson et al, 2010).…”
Section: Reconsolidation = Consolidation?mentioning
confidence: 99%